2009
DOI: 10.1038/ngeo708
|View full text |Cite
|
Sign up to set email alerts
|

Towards absolute plate motions constrained by lower-mantle slab remnants

Abstract: Since the first reconstruction of the supercontinent Pangaea, key advances in plate tectonic reconstructions have been made [1][2][3][4][5][6] . Although the movement of tectonic plates since the start of the mid-Cretaceous period (∼100 million years (Myr) ago) is relatively well understood 1,2 , the longitudinal position of plates before this period is not constrained at all. Here, we use a global mantle tomography model 7 to estimate the longitude of past oceanic subduction zones. We identify 28 remnants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
336
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 364 publications
(373 citation statements)
references
References 26 publications
21
336
0
Order By: Relevance
“…S4 and S5), apart from a small shift due to their slightly differing absolute reference frames. van der Meer et al [2010] suggest a westward shift of the reference frame peaking at 18° at 150 Ma. Applying a corresponding shift to the dipole and quadrupole locations would move divergent quadrupoles closer to the LLSVP centers.…”
Section: Extension Of the Torsvik Et Al [2010] Reconstruction Back Tmentioning
confidence: 99%
“…S4 and S5), apart from a small shift due to their slightly differing absolute reference frames. van der Meer et al [2010] suggest a westward shift of the reference frame peaking at 18° at 150 Ma. Applying a corresponding shift to the dipole and quadrupole locations would move divergent quadrupoles closer to the LLSVP centers.…”
Section: Extension Of the Torsvik Et Al [2010] Reconstruction Back Tmentioning
confidence: 99%
“…4A), generally interpreted as a result of Cretaceous intraoceanic subduction (40,42). Aitchison et al (28) suggested that this anomaly resulted from intraoceanic subduction that terminated with ophiolite obduction onto the leading edge of Greater India.…”
Section: Subduction History and Mantle Tomographymentioning
confidence: 99%
“…By imaging subducted slabs deep in the mantle, which attest to whole-mantle convection and stirring, seismic tomography indicates that the latter is true on planet Earth (Grand et al, 1997;van der Meer et al, 2010). Although compositional heterogeneity has been identified in the lowermost mantle and is potentially linked to MO freezing processes (Garnero and McNamara, 2008;Hernlund and McNamara, 2015;Tackley, 2012), it does not exceed ~3% of the mantle's volume (Hernlund and Houser, 2008).…”
Section: Introductionmentioning
confidence: 99%